Sharks and Skates: Ecology, Distribution and Conservation - Marongiu, Martina Francesca (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Chondrichthyes (sharks, skates, rays, and chimaeras) represent one of the oldest and most ecologically various vertebrate lineages. These predators occupy the top of aquatic food webs and play important functional roles in the control of coastal and oceanic ecosystem structure and function; however, nowadays, overfishing and habitat degradation are altering their populations, leading to a worrisome decline in these species worldwide because of their low resilience due to their K-selected life history strategy (e.g., slow growth, late attainment of sexual maturity, long life spans, and low fecundity). Moreover, data on the stock status of this important resource still remain poor or non-existent, which is due to a problematic taxonomy (e.g., misidentification issues). In these regards, collecting information about these species is essential to formulate conservation strategies to preserve this precious marine resource. In this Special Issue, we aimed to expand the knowledge about these important predators. We have collected data from several parts of the Atlantic and Pacific Oceans and the Mediterranean Sea. The main topics presented in this Special Issue are as follows: abundance and distribution of a single species or more, genetic information using different techniques, life histories (e.g., reproduction, age, and growth), demographic analyses, information about stock assessment, aggregative behaviors, and prey discrimination.